The potential of a novel support vector machine trained with modified mayfly optimization algorithm for streamflow prediction - Adnan R.M.; Kisi O.; Mostafa R.R.; Ahmed A.N.; El-Shafie A. (Taylor and Francis Ltd., 2023)
Balancing; Forecasting; Stream flow; Support vector machines; Exploitation and explorations; Machine learning models; Optimisations; Optimization algorithms; Prediction modelling; Simulated annealing integrated with mayfly optimization; Streamflow prediction; Support vector regression models; Support vector regressions; Support vectors machine; Simulated annealing; algorithm; mayfly; optimization; prediction; streamflow; support vector machine; Jhelum River